Association analysis of the rs4891 genetic variant with the risk of age-related hearing loss: a case-control study - Ali Karimian; Mohammad Karimian (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Age-related hearing loss (ARHL) is thought to be linked to an increase in oxidative stress in the cochlea. Glutathione S-transferase enzymes (GSTs) play a crucial role as antioxidant enzymes in the cochlea. The aim of this study was to evaluate the association between the rs4891 polymorphism in the GSTP1 gene and the risk of ARHL. Methods: This case-control study involved the examination of 90 individuals with ARHL and 100 healthy individuals. Genomic DNA was extracted from blood samples, and the PCR-RFLP technique was used to determine the genotypes of the GSTP1-rs4891 polymorphism. Logistic regression analysis was conducted to investigate the relationship between genotypes and the risk of ARHL. The odds ratio and 95% confidence interval were calculated. Results: The results showed that the TC and CC genotypes were not found to be associated with the risk of ARHL. However, analysis using the dominant model revealed that C allele carriers were at a higher risk of ARHL (P=0.032, 95% CI=0.94-3.23, OR=1.882). Allelic analysis also indicated an association between the C allele and ARHL (P=0.019, 95% CI=1.09-2.65, OR=1.700). Moreover, the CT (P=0.0181, 95% CI=7.8927-1.2127, OR=3.0938) and CC (P=0.0029, 95% CI=64.6308-2.3695, OR=12.3750) mutant genotypes were associated with an increased risk of ARHL with increasing age. Conclusion: The findings suggest that the GSTP1-rs4891 polymorphism may serve as a molecular risk factor for ARHL, particularly in older individuals. However, further studies with larger sample sizes are warranted to validate these findings.